Development of SYBR Green I-based polymerase chain reaction for feline bocavirus 1 detection - Wang, Yong (3 Biotech, 2021)
Feline bocavirus 1 (FBoV-1) may be associated with diarrhea in cats. In this study, a SYBR Green I-based quantitative polymerase chain reaction (qPCR) assay was established to detect FBoV-1. The melting curve showed a single melting peak at 83.0 ℃. The results of sensitivity showed that the detection limit of the qPCR was 3.87 × 10(1) copies/μL. Of note, the detection limit of the conventional polymerase chain reaction (cPCR) was 3.87 × 10(3) copies/μL. The highest intra-assay and inter-assay coefficients of variation (CV%) were 0.98% and 1.42%, respectively. The positive detection rate of 128 clinical samples using the qPCR and the cPCR was 7.0% (9/128) and 4.7% (6/128), respectively. Taken together, these results indicated that the established qPCR assay has good sensitivity, high specificity, and good reproducibility. Therefore, it could provide support for the rapid and efficient clinical detection of FBoV-1.